Dialek Quraisy dalam Kajian Linguistik: Peran Terhadap Perkembangan Bahasa Arab Pra-Islam - Nur Faizatul Ulya; Ainur Rofiq Sofa (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines the linguistic characteristics of the Quraysh dialect and its influence on the development of the pre-Islamic Arabic language. Using a qualitative research method based on a literature review, this study analyzes various sources discussing the phonology, morphology, and syntax of the Quraysh dialect and its role in the formation of standard Arabic. The findings reveal that the Quraysh dialect has a smoother phonological system, a more structured grammar, and a richer vocabulary compared to other Arabic dialects. Its influence became more significant after being used in the Qur’an, which served as the primary reference in the development of standard Arabic. Additionally, classical linguists adopted the Quraysh dialect as the foundation for Arabic grammatical rules. Thus, the Quraysh dialect plays a central role in the evolution of the Arabic language from the pre-Islamic era to the modern period.